Predictive power of 24-h ambulatory pulse pressure and its components for mortality and cardiovascular outcomes in 11 848 participants recruited from 13 populations - Gavish, Benjamin; Bursztyn, Michael; Thijs, Lutgarde; Wei, Dong-Mei; Melgarejo, Jesus D; Zhang, Zhen-Yu; Boggia, José; Hansen, Tine W; Asayama, Kei; Ohkubo, Takayoshi; Kikuya, Masahiro; Yang, Wen-Yi; et al. (Journal of hypertension, 2022)
BACKGROUND: The role of pulse pressure (PP) 'widening' at older and younger age as a cardiovascular risk factor is still controversial. Mean PP, as determined from repeated blood pressure (BP) readings, can be expressed as a sum of two components: 'elastic PP' (elPP) and 'stiffening PP' (stPP) associated, respectively, with stiffness at the diastole and its relative change during the systole. We investigated the association of 24-h ambulatory PP, elPP, and stPP ('PP variables') with mortality and composite cardiovascular events in different age classes. METHOD: Longitudinal population-based cohort study of adults with baseline observations that included 24-h ambulatory BP. Age classes were age 40 or less, 40-50, 50-60, 60-70, and over 70 years. Co-primary endpoints were total mortality and composite cardiovascular events. The relative risk expressed by hazard ratio per 1SD increase for each of the PP variables was calculated from multivariable-adjusted Cox regression models. RESULTS: The 11 848 participants from 13 cohorts (age 53 ± 16 years, 50% men) were followed for up for 13.7 ± 6.7 years. A total of 2946 participants died (18.1 per 1000 person-years) and 2093 experienced a fatal or nonfatal cardiovascular event (12.9 per 1000 person-years). Mean PP, elPP, and stPP were, respectively, 49.7, 43.5, and 6.2 mmHg, and elPP and stPP were uncorrelated ( r = -0.07). At age 50-60 years, all PP variables displayed association with risk for almost all outcomes. From age over 60 years to age over 70 years, hazard ratios of of PP and elPP were similar and decreased gradually but differently for pulse rate lower than or higher than 70 bpm, whereas stPP lacked predictive power in most cases. For age 40 years or less, elPP showed protective power for coronary events, whereas stPP and PP predicted stroke events. Adjusted and unadjusted hazard ratio variations were similar over the entire age range. CONCLUSION: This study provides a new basis for associating PP components with outcome and arterial properties in different age groups and at different pulse rates for both old and young age. The similarity between adjusted and unadjusted hazard ratios supports the clinical usefulness of PP components but further studies are needed to assess the prognostic significance of the PP components, especially at the young age.
Keywords: senioři; krevní tlak; Hypertension; Cohort Studies; Middle Aged; mužské pohlaví; Adult; kohortové studie; systola; Cardiovascular Diseases; ženské pohlaví; Blood Pressure; Humans; ambulantní monitorování krevního tlaku; lidé středního věku; hypertenze; Systole; dospělí; Female; Aged; Blood Pressure Monitoring, Ambulatory; kardiovaskulární nemoci; lidé; Male